THE GENUS MURICOCOCCUM Chun & How (Euphorb.) - KOSTERMANS, A.J.G.H (REINWARDTIA, 1961)
The monotypical genus Muricococcum was published in 1956 (in Acta Phytotaxonomica Sinica 5: 14) with a latin and Chinese diagnosis.